2012
DOI: 10.1155/2012/673637
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Laden Alveolar Macrophages and pH Monitoring in Gastroesophageal Reflux-Related Respiratory Symptoms

Abstract: Lipid-laden alveolar macrophages and pH monitoring have been used in the diagnosis of chronic aspiration in children with gastroesophageal reflux (GER). This study was conducted to prove a correlation between the detection of alimentary pulmonary fat phagocytosis and an increasing amount of proximal gastroesophageal reflux. It was assumed that proximal gastroesophageal reflux better correlates with aspiration than distal GER. Patients from 6 months to 16 years with unexplained recurrent wheezy bronchitis and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The association between aspiration and LLMI has been previously evaluated in children with some studies reporting a positive correlation [18,25] and suggesting that particular cut-off values may be a useful diagnostic test [26]. However, other studies have failed to confirm that LLMI, measured in lavage fluid or sputum, is an indicator of GORD [18,27], highlighting a lack of specificity to detect reflux-related respiratory disease [28]. In adults, LLMI has been proposed as a marker for aspiration pneumonia [10].…”
Section: Discussionmentioning
confidence: 99%
“…The association between aspiration and LLMI has been previously evaluated in children with some studies reporting a positive correlation [18,25] and suggesting that particular cut-off values may be a useful diagnostic test [26]. However, other studies have failed to confirm that LLMI, measured in lavage fluid or sputum, is an indicator of GORD [18,27], highlighting a lack of specificity to detect reflux-related respiratory disease [28]. In adults, LLMI has been proposed as a marker for aspiration pneumonia [10].…”
Section: Discussionmentioning
confidence: 99%
“…The LLM index was significantly lower in the surgical group. Opposing the reliability of LLM index as a marker of microaspiration, Kitz et al 27 conducted a study in children with GERD related respiratory symptoms and found no association between reflux events and LLM counts. But MII was not used in this study, and also underlying pulmonary disease of the selected patient population may cause more reduction in sensitivity and specificity of LLM index.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HMII (24-h multichannel intraluminal impedance) allows the measurement of bolus reflux, which provides more accurate identification of both acidic and weak acidic reflux [39]. Microaspiration may be indirectly suggested by the presence of GER [40], decreased bronchial mucosal pH [9], altered biomarker levels (e.g., pepsin, bile acids, lactate dehydrogenase, and C-reactive protein) [9, 10] or the detection of lipid-laden [55] or chlorophyllin-stained macrophages [56] in BALF, spectra of exhaled breath condensate [51, 57], induced sputum biomarkers, or atypical lung pathology [36]. A clinical trial (NCT trial No.…”
Section: Diagnosis Of Gerd and Microaspiration In Patients With Ipfmentioning
confidence: 99%